Mechanisms mediating the contribution of ecosystem services to human well-being and resilience - Fedele, G.; Locatelli, Bruno; Djoudi, H. (Elsevier, 2017)
Human benefits from ecosystems result from complex interactions between ecological and social processes. People affect ecosystems' capacity to deliver services that contribute to the well-being of humans and their resilience. The delivery of ecosystem services (ES) has often been considered as a linear and direct flow from nature to people without feedbacks or human inputs. We adjusted the widely used ES cascade to highlight how humans mediate each step in the ES delivery. We then applied the proposed framework to empirical field studies in Indonesia. We focused on the role of forested landscapes to increase rural people's resilience to climate hazards such as drought and floods. We found that human actions determine benefits from ES through several mechanisms (ES management, mobilization, allocation-appropriation, and appreciation). These mechanisms are influenced by peoples' decisions along the ES cascade, which depend on specific factors related to rules, assets, values, and spatial context. By facilitating or hindering ES flows, some stakeholders can determine who benefits from ES and influence the well-being of others. A better understanding of the mediating mechanisms, factors, and feedbacks in ES delivery can support the design of sound environmental assessments and sustainable land management practices.